Design Of Asset Data Collection System At PT. Torganda Using Web Technology - Venny Sitorus, Royda; Suherman; Nasution, Hafni (Cattleya Darmaya Fortuna, 2025)
This study presents the design and implementation of a web-based asset data collection system at PT. Torganda to address inefficiencies caused by manual asset management methods. The system integrates Flutter for the user interface and PocketBase for real-time backend data processing, aiming to enhance data accuracy, accessibility, and transparency. Research stages include problem analysis, system design, implementation, testing, and maintenance. Key features such as digital input forms, asset categorization, report generation, and secure user authentication support centralized and structured asset recording. The system significantly reduces human error and improves operational efficiency, contributing to digital transformation within the company's asset management processes